An Integrated Risk Management Model for Performance Assessment of Airport Pavements: The Case of Istanbul Airport - Seven, Eyyup; Yardim, Mustafa Sinan (MDPI, 2024)
Effective management of airport pavements is essential for maintaining safety and operational efficiency in air travel. An airport pavement management system (APMS) operates at two levels: the network level, which monitors overall pavement performance across the airport, and the project level, which conducts detailed inspections of individual pavements. However, pavement assessments are often costly and labor intensive, necessitating the development of cost-effective and practical models. This paper introduces the Airport Pavement Integrated Risk Management (APIRM) model, which integrates pavement condition assessment criteria with safety risk management (SRM) methodologies. The model was applied at Istanbul Airport. By using APIRM, airports can prioritize high-risk areas, optimizing resource allocation and enhancing safety. The model encourages coordination among various airport departments, offering a holistic approach to pavement management that integrates maintenance requirements with safety considerations.
Keywords: airport pavement management system; performance evaluation; FAA Paser; friction; roughness; safety risk management; Istanbul Airport; Chemistry; Engineering; Materials Science; Physics